FOREST RESEARCHES IN THE WORLD - Shalaev, Valentin (Innovation in Woodworking Industry and Engineering design, 2012)
The directions of the forest researches are considered in the paper. They give in accord-ance to the estimation of the IUFRO-experts for the period of time from XXII up to XXIII World Congress IUFRO. These researches priorities may be taken into account while plan-ning the science development in the country. The paper provides the short information on research priorities stated be the EU Seventh Framework Programme.